2011
DOI: 10.1016/j.jpainsymman.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Hospice Referrals and Code Status: Outcomes of Inpatient Palliative Care Consultations Among Asian Americans and Pacific Islanders With Cancer

Abstract: Context Intensive palliative care consultations for plan of care may reduce racial differences in end-of-life care. Objectives To compare cancer patients’ hospice referrals and code status changes after inpatient palliative care consultations by patient ethnicity and consultation intensity. Methods This observational cohort study prospectively recorded data for all adult cancer patients receiving palliative care consultations at the largest teaching hospital in Hawaii from 2005 through 2009. Chi-square ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 31 publications
3
51
0
Order By: Relevance
“…In another previous study, almost 40% of the spouse caregivers reported depressive symptoms in a range that was likely to be clinically significant, a prevalence that was almost two-fold than their ill partners (Rittenberger et al, 2011). Previous studies have demonstrated that caregivers of patients with cancer have increased health problems and psychosocial stress (Bergen-Jackson et al, 2009;Kiely et al, 2010;Zhou et al, 2010;Bell et al, 2011;Gilbertson-White et al, 2011;Legler et al, 2011;Stevens et al, 2011). Therefore, in palliative care, care burden could have a bad impact on caregivers.…”
Section: Discussionmentioning
confidence: 97%
“…In another previous study, almost 40% of the spouse caregivers reported depressive symptoms in a range that was likely to be clinically significant, a prevalence that was almost two-fold than their ill partners (Rittenberger et al, 2011). Previous studies have demonstrated that caregivers of patients with cancer have increased health problems and psychosocial stress (Bergen-Jackson et al, 2009;Kiely et al, 2010;Zhou et al, 2010;Bell et al, 2011;Gilbertson-White et al, 2011;Legler et al, 2011;Stevens et al, 2011). Therefore, in palliative care, care burden could have a bad impact on caregivers.…”
Section: Discussionmentioning
confidence: 97%
“…11,12 In our team's experience, many elderly patients in the hospital have an unstated plan of care that seeks cure and life prolongation. As a patient with serious or complex illness worsens, it may become clear to the health care team that the curative, life-prolonging plan of care is no longer achievable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent observational cohort study of patients with cancer who received palliative care consults found that comprehensive consults (involving a plan of care discussion as well as symptom management) were associated with an increased likelihood of hospice referral. 43 Ensuring access to palliative care, particularly when a patient has not yet met the eligibility requirements for hospice, may help to increase hospice use in this population.…”
Section: Discussionmentioning
confidence: 99%